PROSES PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Rahmat rahmat; Mujahidin Almubarak (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2021)
ABSTRACT: This article aims to study the theoretical process of developing the Islamic Education Curriculum as well as to what extent is the curriculum with Islamic education in the process, while in the process it takes a long time to perfect the curriculum with Islamic religious education, while curriculum development is designed with ideas and programs, The idea is in the form of a document in the form of a syllabus, then with the process of development will be developed and socialization of the community and educational institutions. The process of this educational curriculum can be developed by designing, implementing, and perfecting the Islamic religious education curriculum. in the form of curriculum there are four dimensions, namely the idea of design, implementation, and the results are involved by extracurricular and curricular.